Spatiotemporal analysis of retail: pre- and post-COVID dynamics in Gros, San Sebastian - Berra-Sandín, Mikel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
The decrease of commercial activity that has been occurring in the last decade has recently accentuated by the COVID pandemic, affecting the livability of cities and public space. This paper analyzes the ground floor activities in Gros neighbourhood, in San Sebastian, Spain, observing both its temporal evolution and its spatial distribution. The study performs two in situ geolocation data collections in January and August 2020, immediately before and after the COVID lockdown in Spain. Through the collected data, it analyzes the distribution and evolution of ground floor space dedicated to public activities. The study concludes that the activities suffered a decrease of 1.8% in the analyzed period, and that activities located on pedestrianized streets or with fewer lanes have had fewer closures. The work also shows which efforts are needed for in situ data collection to guide urban policy.